The 2011–2014 Pollino Seismic Swarm: Complex Fault Systems Imaged by 1D Refined Location and Shear Wave Splitting Analysis at the Apennines–Calabrian Arc Boundary - Pastori, Marina; Margheriti, Lucia; De Gori, Pasquale; Govoni, Aladino; Lucente, Francesco Pio; Moretti, Milena; Marchetti, Alessandro; Di Giovambattista, Rita; Anselmi, Mario; De Luca, Paolo; Nardi, Anna; Agostinetti, Nicola Piana; et al. (Frontiers in Earth Science, 2021)
In the years between 2011 and 2014, at the edge between the Apennines collapsing chain and the subducting Calabrian arc, intense seismic swarms occurred in the Pollino mountain belt. In this key region, <2.5 mm/yr of NE-trending extension is accommodated on an intricate network of normal faults, having almost the same direction as the mountain belt. The long-lasting seismic release consisted of different swarm episodes, where the strongest event coinciding with a ML 5.0 shock occurred in October 2012. This latter comes after a ML four nucleated in May 2012 and followed by aseismic slip episodes. In this study, we present accurate relocations for ∼6,000 earthquakes and shear-wave splitting analysis for ∼22,600 event-station pairs. The seismicity distribution delineates two main clusters around the major shocks: in the north-western area, where the ML 5.0 occurred, the hypocenters are localized in a ball-shaped volume of seismicity without defining any planar distribution, whilst in the eastern area, where the ML 4.3 nucleates, the hypocenters define several faults of a complex system of thrusts and back-thrusts. This different behavior is also imaged by the anisotropic parameters results: a strong variability of fast directions is observed in the western sector, while stable orientations are visible in the eastern cluster. This tectonic system possibly formed as a positive flower structure but as of today, it accommodates stress on normal faults. The deep structure imaged by refined locations is overall consistent with the complex fault system recently mapped at the surface and with patterns of crustal anisotropy depicting fractures alignment at depth. The possible reactivation of inherited structures supports the important role of the Pollino fault as a composite wrench fault system along which, in the lower Pleistocene, the southward retreat of the ionian slab was accommodated; in this contest, the inversion of the faults kinematics indicates a probable southward shift of the slab edge. This interpretation may help to comprehend the physical mechanisms behind the seismic swarms of the region and defining the seismic hazard of the Pollino range: nowadays a region of high seismic hazard although no strong earthquakes are present in the historical record.